2018
DOI: 10.1002/adsc.201800802
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Promoted 2‐Bromotetrafluoroethylation of Nitrones

Abstract: A reaction of nitrones with 1,2-dibromotetrafluoroethane affording bromodifluoroethylsubstituted hydroxylamines is described. The process is performed in the presence of a ruthenium photocatalyst and ascorbic acid as a stoichiometric reducing agent and is mediated by blue light irradiation. The fluroalkylation products can undergo chemoselective transformations involving either NÀO or CÀBr bonds furnishing various tetrafluorinated compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In case of 3n there was some unidentified side product formed under the standard conditions. In the previous research on the radical addition to nitrones we sometimes encountered a fluoroalkylation of the aromatic rings, if an excess of the fluorinated alkyl iodide was used [22][23][24]. This prompted us to attempt the reaction with an equimolar amount of the iodide 2b, which resulted in a cleaner process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of 3n there was some unidentified side product formed under the standard conditions. In the previous research on the radical addition to nitrones we sometimes encountered a fluoroalkylation of the aromatic rings, if an excess of the fluorinated alkyl iodide was used [22][23][24]. This prompted us to attempt the reaction with an equimolar amount of the iodide 2b, which resulted in a cleaner process.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we disclosed a photoredox method for the reductive radical fluoroalkylation of nitrones [22][23][24]. We have also eval- uated the construction of fluorinated tetrahydroisoquinoline structures starting from nitrones, but this required four consecutive reactions with different conditions and chromatographic separation at each step [25] (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Dilman et al showed that fluorides containing hydroxylamines can be obtained by addition of a radical derived from 1,2-dibromotetrafluoroethane to nitrones under photocatalytic conditions. 67 The resulting hydroxylamine can be benzoylated and then used as a substrate in a coppercatalyzed electrophilic cross-coupling with phenylaluminum reagent (prepared in situ from phenylmagnesium chloride and Et 2 AlCl, Scheme 52).…”
Section: 24mentioning
confidence: 99%
“…Radical addition at the CN bond is an important process, serving as a key step in many synthetic methods. , These reactions have become even more popular due to the advent of photoredox catalysis, which provided convenient ways for the generation of free radicals. Indeed, photocatalytic reactions of azomethines with alkyl halides, redox active esters, sulfinates and sulfides, the C–H bond, borates, and siliconates have been described . Herein we report that difluoroboryl complexes 2 can serve as efficient acceptors of alkyl radicals (Scheme ).…”
mentioning
confidence: 95%